Association of Myostatin Gene with On-field Sporting Traits of Indigenous Cattle Breeds (Bos indicus) of Tamil Nadu - Priyadharsini, Ramadhas; Gopinathan, Alagappan; Karthickeyan, Sarojini M. K.; Jagatheesan, Pitchai N. R. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Sports genomics is considered a branch of molecular genetics, which is used to identify the candidate genes associated with domesticanimals’ sporting traits, especially in horses, dogs, and cattle, to select animals with the best sporting ability. Blood samples werecollected from indigenous bulls (n=233) used for a sporting event in Tamil Nadu for genomic DNA isolation. Molecular characterization ofMyostatin gene, including its promoter region, was carried out to find the sequence variation. Compared with the Bos indicus sequence,two variations were detected in exon 1 and exon 3 and no variation in exon 2. The intronic regions were found to have single base pairvariations, single base-pair insertions, and 12 to 16 bp insertions. In addition, nine types of variations found in the promotor region and the genotyping of SNP at position -644 revealed the predominance of genotype CC with the estimated frequencies of 0.81, 0.69, 1.00, and 0.80 in Pulikulam, Kangayam, Umblachery, and non-descript bulls, respectively. TT genotype had higher mean velocity and highest time spent within the boundary of bull tamers, and CC genotype had higher stride length. In conclusion, it could be inferred that the Myostatin gene would be used as a marker for sporting traits, but it needs extensive study to validate its role in regulating sporting traits
Keywords: : Bos indicus; Indigenous cattle breeds; Jallikattu; ,Myostatin gene; Sporting traits